Mystery at the Washington Monument - Roy, Ron, 1940- (Roy, Ron, 1940- Capital mysteries, 2007)
When KC and Marshall see lights flickering at night in the Washington Monument, their investigation turns up a monkey, a hole in one of the monument stones, and a hundred-year-old mystery.